Investigating Iraqi EFL College Students' Multiple Intelligences - شدى السعدي شهد حاتم (College of Education for Women, 2019)
Various theories on learning have been developed with increasing frequency in the last few decades. In tandem with this, Multiple Intelligence theory appeared as a new approach to education as well as an important theory in the field of language learning. Gardner explains that all human beings have different intelligence fields and a potential to develop them. These intelligences are (verbal-linguistic, logical-mathematical, visual-spatial, musical, bodilykinesthetic, interpersonal, intrapersonal, naturalistic, and Existential). This study aims at investigating Multiple Intelligences of Iraqi college EFL students. To achieve the aims of the study, a questionnaire is adopted according to Birmingham model which includes 40 items with a five point scale (this is not like me at all, this is a bit like me, this is sometimes like me, I am like this more often than not, I am always like this), and covers all types of Multiple Intelligence theory. The sample of the present study consists of the first and second year female students from Department of English Language, College of Education for Women/ University of Baghdad. After ensuring the validity and reliability of the questionnaire, the researchers have applied the questionnaire on 18th of May 2014. The results show that most of the Iraqi college students prefer music with learning, as well as, musical, intrapersonal and interpersonal intelligences as they most frequently used and accepted. Finally, conclusions, recommendations and suggestions for future work are put forward. Key Terms: Multiple Intelligences Theory, Learning.